1980
DOI: 10.1073/pnas.77.9.5163
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir inhibition of Epstein-Barr virus replication.

Abstract: Acyclovir [92-hydroxyethoxymethyl)guanineJ triphosphate inhibits Epstein-Barr virus (EBV)associated DNA polymerase (DNA nucleotidyltransferase; EC 2.7.7.7) to a greater extent than it inhibits host a and jB DNA polymerases. The affinity of the compound for viral polymerase is 100-fold higher than for a-polymerase. Selective prevention of virus replication can be attained by compounds that inactivate the novel enzymes necessary for virus growth. Virus-specific DNA polymerase (deoxynucleoside triphosphate:DNA nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
1
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 28 publications
0
53
1
1
Order By: Relevance
“…32,33) Hence, anti-herpes drugs that are commonly used such as acyclovir and ganciclovir, are nucleoside analogs, suppress the function of herpes DNA polymerase and viral lytic DNA replication. 12,34,35) An earlier study demonstrated that EBV virions that are produced by B lymphocytes exhibit a tropism by which they preferentially infect epithelial cells. 33) Therefore, the lytic reactivation of EBV in B lymphocytes may be an important step toward the oncogenesis of epithelial cell that is associated with EBV, including nasopharyngeal carcinoma.…”
Section: Fig 2 Indirect Immunofluorescence Analysis Of the Inhibitomentioning
confidence: 99%
“…32,33) Hence, anti-herpes drugs that are commonly used such as acyclovir and ganciclovir, are nucleoside analogs, suppress the function of herpes DNA polymerase and viral lytic DNA replication. 12,34,35) An earlier study demonstrated that EBV virions that are produced by B lymphocytes exhibit a tropism by which they preferentially infect epithelial cells. 33) Therefore, the lytic reactivation of EBV in B lymphocytes may be an important step toward the oncogenesis of epithelial cell that is associated with EBV, including nasopharyngeal carcinoma.…”
Section: Fig 2 Indirect Immunofluorescence Analysis Of the Inhibitomentioning
confidence: 99%
“…Furthermore. ACV can inhibit EBV replication in superinfected Raji or EBV virus producer Iymphoblastoid cell lines (Datta et al, 1980;Colby et al, 1981). These studies have shown that ACV can be used to distinguish between latent and chronic persistence and is therefore an important tool in studying the mechanisms of persistence of herpesviruses.…”
Section: Introductionmentioning
confidence: 99%
“…During the lytic form of viral replication, EBV uses a virally encoded DNA polymerase and the oriLyt replication origin to duplicate its genome (24,36,51). The lytic form of EBV replication can be effectively inhibited in vitro by the guanine nucleoside analogues, acyclovir (ACV) and ganciclovir (GCV) (11,16,50,56). Since acyclovir is significantly less toxic than ganciclovir in patients, acyclovir is generally used to treat diseases associated with lytic EBV infection, such as oral hairy leukoplakia (3).…”
mentioning
confidence: 99%